2013
DOI: 10.5430/elr.v1n1p118
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Using Summarization Strategies on Iranian EFL Learners' Reading Comprehension

Abstract: It is already known that for being effective readers we need explicit strategy training and it is generally agreed that well-developed reading comprehension ability is the key to students' academic success .This comprehension ability is not a passive state which one possesses, but it is an active mental process which needs to be nurtured and improved. The study aims to explore the effectiveness of using summarization strategies makes any significant difference in EFL learners' level of comprehending English te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
3
7
0
1
Order By: Relevance
“…The results of the study showed that having achieved an awareness of summarizing strategy, students can have a better command of a variety of practices that they can use for successful summaries of the passages. The findings of this study in line with the other researchers (Aghaei, & Zhang, 2012;Al-Nujaidi, 2003;Al-Seweed, 2000;Jitendraa, et al, 2006;Karbalaei & Rajyashree, 2010;Pakzadian & Eslami Rasekh, 2012;Shang, 2010;Sheorey et al, 2008;) showed that reading comprehension tests can help the students to follow the steps of the summarizing process to identify topics, main ideas, and details, and to write summaries. It can be concluded that when students are exposed to summarizing strategy, they become aware of the processes that can be applied in better understanding the reading passages and they can view the passage as a whole unit in which knowledge of the parts can be attained by paying attention to the preceding and following sections of the passage.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the study showed that having achieved an awareness of summarizing strategy, students can have a better command of a variety of practices that they can use for successful summaries of the passages. The findings of this study in line with the other researchers (Aghaei, & Zhang, 2012;Al-Nujaidi, 2003;Al-Seweed, 2000;Jitendraa, et al, 2006;Karbalaei & Rajyashree, 2010;Pakzadian & Eslami Rasekh, 2012;Shang, 2010;Sheorey et al, 2008;) showed that reading comprehension tests can help the students to follow the steps of the summarizing process to identify topics, main ideas, and details, and to write summaries. It can be concluded that when students are exposed to summarizing strategy, they become aware of the processes that can be applied in better understanding the reading passages and they can view the passage as a whole unit in which knowledge of the parts can be attained by paying attention to the preceding and following sections of the passage.…”
Section: Discussionsupporting
confidence: 90%
“…Often, they face problems even with the typical question and answer format that is provided after they read a passage. Research (Dole, Brown, & Trathen, 1996;Janzen, 2003;Karbalaei & Rajyashree, 2010;Khoshsima & Rezaeian Tiyar, 2014;Pakzadian & Eslami Rasekh, 2012;Nurhayati, 2014;Roohani, et al, 2015;Deshpande, 2016;Teng. 2016;Damayanti, 2017) has shown that together with direct instructions when students are taught reading strategies this will improve not only their comprehension of the reading passage but also their performances on the tests.…”
Section: Introductionmentioning
confidence: 99%
“…There were no inadequate students in terms of "meaning integrity, plot, secondary ideas, and details, use of key words, direct citation or imitation" criteria. The "introduction sentence" was the criteria which the greatest numbers of students were at an inadequate level (7). The results of this study mostly overlap with the study conducted by Benzer et al [27].…”
Section: Summarization Successsupporting
confidence: 63%
“…Summarization provides a significant contribution to students in understanding information and transferring it to long-term memory, as well as improving memory and understanding by ensuring effective use of mental skills [1]. Studies show that students who are successful in reading comprehension are also successful in summarization [2,3] and that teaching of summarization strategies increases comprehension [4][5][6][7][8]48] and enables the things learned to be permanent [9,48]. Understanding and remembering are quite important for academic success.…”
Section: Introductionmentioning
confidence: 99%
“…Birçok çalışmada cinsiyetin özetleme başarısı üzerinde etkisi olup olmadığı sorgulanmıştır. Yapılan çalışmaların bir bölümü kız öğrencilerin (Ülper & Okuyan, 2010;Başkan, 2019;Eroğlu, 2019;Çetin & Bulut, 2020;Çetinkaya, Şentürk & Dikici, 2020) bir bölümü erkek öğrencilerin (Erdem, 2012) daha başarılı olduğuna bir bölümü de cinsiyetin etkisi olmadığına (Pakzadian & Rasekh, 2012;Bıyıklı & Doğan, 2015;Görgen & Altıntaş, 2015;Zenci, 2020) işaret etmektedir. Bu çalışmanın sonuçlarına göre özet metnin giriş, temel olaylar ve sonuç bölümlerini yazma ve özet metnin genel puan ortalamaları açısından kız ve erkek öğrenciler arasında anlamlı bir fark bulunmamıştır.…”
Section: Tartişma Ve Sonuçunclassified